What is Peace Engineering? - Jordan, Ramiro; Martinez-Ramon, Manel; Koechner, Donna; Agi, Kamil (Conference proceedings : Midwest Symposium on Circuits and Systems, 2024)
The Ibero-American Science and Technology Education Consortium (ISTEC) created in 1990 is the outcome of an Engineering Education research effort led by University of New Mexico Electrical & Computer Engineering faculty (UNM-ECE) and funded by Motorola, Inc., to be a catalyst for technological, social, cultural, policy, and socio-economic development. We envisioned STEM as the common language for practical global Peace Engineering (PENG) and stress sharing resources (data, technology, services, etc.) through alliances among academia, industry, government agencies and multilateral organizations. ISTEC co-organized the International Federation of Engineering Education Societies (IFEES, 2006), the Global Engineering Deans Council (GEDC, 2008) and the first Global Peace Engineering Conference, WEEF-GEDC 2018, hosted by UNM School of Engineering. During the 2018 event, a new definition of Peace Engineering emerged and the Peace Engineering Consortium (PEC) was formed. In addition to global PENG workshops and presentations, PENG tracks are now in every annual ISTEC and WEEF-GEDC event. Partnering with the PEC, UNM-ECE created a PENG Minor in 2020 covering topics that include ethics, sustainability, society, JEDAI, design thinking, analytics and AI. We encourage cross-disciplinary collaboration to break academic silos and apply this knowledge to real world situations.